Synthesis and Characterization of Hydrogel from Gongronema latifolium for Potential Drug Delivery - J., Amadi I.; A., Attah D.; J, Ugye T.; S., Ikpatim; J., Aasegh T. (African Journal of Clinical Medicine and Pharmacy Research, 2025)
This study investigates the synthesis and characterization of a plant-based hydrogel derived from Gongronema latifolium leaf extracts for potential drug delivery applications. Bioactive compounds—alkaloids, flavonoids, terpenoids, and saponins—were extracted using standard phytochemical methods. The biocompatible hydrogel was synthesized using polyvinyl alcohol (PVA) and polyethylene glycol (PEG) monomers and subsequently characterized by UV-Visible spectroscopy, Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetric Analysis (TGA), Scanning Electron Microscopy (SEM), and X-Ray Diffraction (XRD). The results confirmed successful incorporation of the plant extracts into the hydrogel matrix, forming a porous, interconnected 3D polymer network. TGA analysis indicated good thermal stability, bioactivity, and a semi-crystalline structure with high entrapment efficiency—features desirable for controlled drug delivery, water retention, and solute diffusion. FTIR spectra confirmed the presence of hydroxyl and carbonyl functional groups, suggesting strong hydrogen bonding and effective polymeric crosslinking. SEM imaging revealed a rough, heterogeneous surface with interconnected pores, while XRD analysis indicated predominantly amorphous characteristics with slight crystallinity. The findings demonstrate the successful development of a structurally stable and bioactive hydrogel with promising therapeutic and agricultural applications. The hydrogel offers a sustainable alternative to conventional petrochemical-based materials, aligning with eco-friendly innovation in drug delivery systems.